The Effect of Lecture Method with Leaflet Distribution on Knowledge of Signs of Labor in Pregnant Women at Community Health Center X: Apriliana Pipin, Marchella Audina, Trivina, Susanna, Yosefin Beni Purbo Utami - Apriliana Pipin; Marchella Audina; Trivina; Susanna; Yosefin Beni Purbo Utami (Jurnal Persada Husada Indonesia, 2026)
Research Objective, Pregnancy classes are important promotive strategies to improve pregnant women's knowledge. A preliminary study found that 60% of pregnant women were unable to correctly identify labor signs, and most reported one-way counseling without engaging media. This study aimed to determine the effect of lecture-based education using leaflets on improving pregnant women's knowledge of labor signs. Methodology, This quantitative study used a pre-experimental one-group pretest–posttest design to assess the effect of the intervention by comparing respondents' knowledge before and after. The research instrument was a questionnaire tested for validity and reliability on 30 pregnant women, with 21 valid items. The intervention consisted of education on signs of labor using leaflets for approximately 20 minutes, involving 40 pregnant women as participants. Results , Lecture-based education combined with leaflets significantly improved pregnant women's knowledge of labor signs. Good knowledge increased from 5% to 35%, while poor knowledge decreased from 42.5% to 5% after the intervention (p = 0.001). Respondents' characteristics, including healthy reproductive age, secondary education, and prior pregnancy experience, supported the intervention success. Conclusion. Lecture and leaflet methods are effective educational strategies to enhance pregnant women's understanding of labor signs.